Health impact of energy use in buildings: Radiation propagation assessment in indoor environment - Mehzabeen Mannan; Yamane W. Weldu; Sami G. Al-Ghamdi (Energy Reports, 2020)
Energy has become an essential part of today's lifestyle, especially for using the electronic appliances in homes, offices and other built environments in a daily basis. Although in modern life, electronic devices have become ubiquitous, the excessive electromagnetic radiations from these appliances may cause potential health effects. Realizing this significance, a systemic and comprehensive assessment was performed to study the radiation propagation generating from the energy based electric appliances. Along with measuring the radiation exposure in buildings, this study examined how the radiation propagation varies with different construction materials. Moreover, radiation associated human health impacts were also investigated. Evaluation of five building environment demonstrated that drywall acted as the best shielding object (transmission coefficient: 18% electric field strength) whereas lumber and glass wall acted as the poor shielding material (96% and 97% electric field strength respectively). Comparison with the standard values specified by international authorities showed lower field strength values for some regulatory institute, although these values were higher compared to some more restricted safety levels in some countries, indicating the possible human health impacts in the assessed built environment. Hence, this study recommends utilization of proper shielding materials, maintaining exposure distance along with exposure duration reduction.
Keywords: 330; Electromagnetic radiation; Green building; Human health; Indoor environmental quality; Spatial design